2020
DOI: 10.1097/cm9.0000000000001257
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of Shexiang Baoxin pill (MUSKARDIA) in patients with stable coronary artery disease: a multicenter, double-blind, placebo-controlled phase IV randomized clinical trial

Abstract: Background: The Shexiang Baoxin Pill (MUSKARDIA) has been used for treating coronary artery disease (CAD) and angina for more than 30 years in China. Nevertheless, methodologically sound trials on the use of MUSKARDIA in CAD patients are scarce. The aim of the study is to determine the effects of MUSKARDIA as an add-on to optimal medical therapy (OMT) in patients with stable CAD. Methods: A total of 2674 participants with stable CAD from 97 hospitals in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(53 citation statements)
references
References 35 publications
3
49
1
Order By: Relevance
“…Shexiang Baoxin pill (MUSKARDIA), as an additional medicine on the basis of standard treatment for patients with stable CAD, can safely reduce the frequency of angina in patients with stable CAD. In addition, MUSKARDIA has a potential effect of decreasing incidence of MACE (major adverse cardiovascular event) in patients with stable CAD [ 20 ]. A total of 2674 participants with stable CAD from 97 hospitals in China were divided into a MUSKARDIA or placebo group and observed for 24 months.…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…Shexiang Baoxin pill (MUSKARDIA), as an additional medicine on the basis of standard treatment for patients with stable CAD, can safely reduce the frequency of angina in patients with stable CAD. In addition, MUSKARDIA has a potential effect of decreasing incidence of MACE (major adverse cardiovascular event) in patients with stable CAD [ 20 ]. A total of 2674 participants with stable CAD from 97 hospitals in China were divided into a MUSKARDIA or placebo group and observed for 24 months.…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…Myocardial I/R injury has a multimodal pathogenesis and thus treatment of I/R injury may require targeting a variety of factors to achieve better results (Davidson et al, 2019;Li et al, 2019). SBP is a traditional compound preparation composed of a variety of Chinese herbs Tian et al (2018), diminishes the level of cardiac troponin T (cTNT) and cardiac troponin I (cTNI) in STEMI patients (Lu et al (2018), significantly decreases the frequency of angina in patients with stable CAD Ge et al (2021), and lower the MACCE in patients with NSTE-ACS (Zhou et al, 2016). However, we confirmed that SBP was able to reduce the myocardial infarction area and relieve I/R injury assessed by SPECT that accurately assessed I/R injury and myocardial infarction area (Bøtker et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of I/R injury is diverse Hausenloy et al (2017) , and cooperative treatment through different mechanisms may be a new approach for I/R injury treatment ( Davidson et al, 2019 ). Shexiang Baoxin Pill (SBP) is a traditional Chinese medicine compound preparation, it is mainly composed of artificial moschus, radix ginseng, calculus bovis artifactus, cortex cinnamomi, styrax, venenum bufonis, and borneolum syntheticum, and is mainly used to treat CHD ( Lu et al, 2018 ; Ge et al, 2021 ). The extract of the components of SBP reduces I/R injury, myocardial remodeling, and myocardial infarction area in animals through multiple mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Modern pharmacological studies have shown that SBP and its active ingredients have pleiotropic effects in protecting the circulatory system, such as promoting therapeutic angiogenesis, restoring myocardial function, reducing inflammation, and improving endothelial dysfunction, which may be necessary for the curative effect of CHD after PCI. At the same time, evidencebased clinical studies have shown that SBP is advantageous as an adjuvant treatment in numerous cardiovascular diseases, such as stable angina, myocardial infarction, and heart failure [7][8][9]. However, the clinical evidence regarding the efficacy of SBP in the treatment of CHD after PCI has not been well summarized yet.…”
Section: Introductionmentioning
confidence: 99%